Implicit Theories of Interest: Finding Your Passion or Developing It?. (October 2018) - O'Keefe, Paul A.; Dweck, Carol S.; Walton, Gregory M.
People are often told to find their passion, as though passions and interests are preformed and must simply be discovered. This idea, however, has hidden motivational implications. Five studies examined implicit theories of interest—the idea that personal interests are relatively fixed (fixed theory) or developed (growth theory). Whether assessed or experimentally induced, a fixed theory was more likely to dampen interest in areas outside people's existing interests (Studies 1–3). Individuals endorsing a fixed theory were also more likely to anticipate boundless motivation when passions were found, not anticipating possible difficulties (Study 4). Moreover, when it became difficult to engage in a new interest, interest flagged significantly more for people induced to hold a fixed rather than a growth theory of interest (Study 5). Urging people to find their passion may lead them to put all their eggs in one basket but then to drop that basket when it becomes difficult to carry.